Impact of core-product and service-encounter quality, attitude, image, trust and love on repurchase: Full-service vs low-cost carriers in South Korea. Issue 4 (8th April 2019) - Han, Heesup; Yu, Jongsik; Chua, Bee-Lia; Lee, Sanghyeop; Kim, Wansoo
Abstract : Purpose: The purpose of this study was to examine airline passengers' repurchase decision-making process by developing a sturdy theoretical framework comprising in-flight core-product and service-encounter quality, brand attitude, image, trust and love. The authors also attempted to examine if such decision formation differs across full-service and low-cost airlines in South Korea. Design/methodology/approach: A quantitative method was used to achieve research objectives. For assessment of the conceptual framework and test of research hypotheses, a structural equation modeling and test for metric invariance were used. Findings: The results revealed that in-flight product and service-encounter quality significantly affected their subsequent variables, and their impact on intention was mediated by brand attitude, image, trust and love. In addition, brand image along with brand trust included the strongest influence on intention. Findings also indicated that the relationships among brand attitude, image, trust and love significantly differed between full-service and low-cost airlines. Practical implications: Increasing the customer retention rate is a key component of airline business success. This study made an important contribution to advancing the existing knowledge on what factors induce airline customers' decision to repurchase a particular airline product and how such factors are interrelated with each other within the proposed model. Originality/value: This research was the first to explore that the relationship strength among brand image, brand attitude, brand trust and brand love are not equal between full-service and low-cost airline passenger groups.